PEMBENTUKAN MODEL LOG LINIER EMPAT DIMENSI (Studi Kasus : Rata-rata Pengguna Jenis Bahan Bakar Minyak berdasarkan Jenis Kendaraan, Rasio Kompresi dan Kapasitas Mesin) - Sari, Juli Sekar; Wilandari, Yuciana; Hoyyi, Abdul (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Based on the data from the Central Bureau of statistics, Indonesia's population is 237 million, an increase of 15.2% of the total population in 2000. With the increasing of the population from year to year, automatically the growth of vehicles will also experience increased. The impact of the increase in the number of motor vehicles is surely in the form of fuel consumption. Moreover, many factors will consider by the people to choose the type of fuel for their vehicle. Those factors included in the internal and external factors of the vehicle itself. At first, the internal factors in question are the type of vehicle, the compression ratio of the engine, and engine capacity. This research was conducted to find out the relationship between the internal factors with the log-linear Models. Log-linear Model was used to analyze the relationship between the variable responsesthat arewhich formed the contingency table. In this case, the researcher used log-linear Model of four dimensions with the step of analysis, as follows: outlining the possible model with diagram’s association, looking for the grade of frequency estimation of hope of any possible model, examining the Goodness of Fit of each model to find out the significant one, and determining the best model, in this case by looking at the smallest value of AIC. From the log-linear Model four dimensions is obtained the best model is the Model (WX, XY, XZ, YZ YZ) which means in case of this research there is a relationship between the type of fuel (W)*type of vehicle (X), the type of vehicle (X)*the compression ratio of the engine (Y), the type of vehicle (X)*engine capacity (Z), and the compression ratio of the engine (Y)*Engine Capacity(Z), with the value of AIC = -184. Keywords:, Log linear models four dimention, AIC